PENGARUH EARNING PER SHARE (EPS), RETURN ON ASSET (ROA), CURRENT RATIO (CR), PRICE BOOK VALUE (PBV) TERHADAP HARGA SAHAM (STUDI KASUS PADA PERUSAHAAN YANG TERDAFTAR PADA LQ45 DI BURSA EFEK INDONESIA (BEI)) - Rindu, Rindu Joshua Parulian Nainggolan; H. Manao, Stephen Cornelius; Sinuraya, Bella Ristha Sinuraya; Nasution, M Irsan (Akuntansi Prima, 2024)
This research aims to test and explain the partial and dominant influence of Earning Per Share (EPS), Return On Assets (ROA), Current Raio (CR), Price Book Value (PBV) on the share prices of companies listed on LQ45 on the Indonesia Stock Exchange (IDX). The analytical method used in this research is a quantitative method by testing classical assumptions and statistical analysis, namely multiple linear regression analysis. The sampling method used was purposive sampling. The variables in this research consist of EPS, ROA, CR and PBV as independent variables, and share price as the dependent variable with a total sample of 60 from 30 companies. The results of the analysis show that EPS and ROA have a significant effect on share prices. while CR and PBV do not have a significant effect on stock returns. For further research, it is hoped that other research variables can be added, for example Net Profit Margin (NPM), Debt to Equity Ratio (DER) or Price Earning Ratio (PER).